Non Disclosure Of HIV Positive Status Of Women To Their Partner : Implication For PMTCT - Anindita, Mita; Shaluhiyah, zahroh (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2013)
The prevalence of HIV virus from mother to baby or Mother to Child Transmission (MTCT) is the largest cause of infant and children infected with HIV / AIDS, which is 90%. This is the result of mother to infant transmission during pregnancy, childbirth and breastfeeding. Without intervention, there is a 20-45% chance that the baby will be born infected with HIV from a mother with HIV. Although many efforts have been carried out over the past few years, PMTCT coverage is still low in Indonesia. Objective of this researvh is to explore non disclosure of HIV positive status of women and the implication for PMTCT program in Semarang City. The method of this research is qualitative study with case study design by purposive sampling for choosing the subject. Interviews were carried out with 3 participants. These were transcribed verbatim and manually analysed using the thematic content analysis.The reasons of nondisclosure HIV status among respondent that was respondent felt that her partner might leave them after know about HIV positive status, the partner might be afraid of HIV from them, their husband might think that their unfaithful because their husband might think that HIV from person with sexual multipartner. The stigma related to HIV/AIDS and the behaviors associated with HIV risk have resulted in significant barriers to nondisclosure HIV status among respondent. All of the respondents didn’t take ARV during pregnant, labour with pervaginam delivery, and they gave formula feeding. Conclusion : Need designing the explicit rules in Central Java to the people who living with HIV/ AIDS who nondisclosure with their partner, health provider and deliberate to transmission her virus to the other. Counselling when VCT also explained about PMTCT focus on dealing with social factors, and behavioural beliefs that impact on disclosure of HIV status. Management should address health system factors that result in non-disclosure of HIV status. Keywords : nondisclosure HIV status, PMTCT, partner